Advancing empirical resilience research. (2nd September 2015) - Kalisch, Raffael; Müller, Marianne B.; Tüscher, Oliver
Abstract: We are delighted by the broad, intense, and fruitful discussion in reaction to our target article. A major point we take from the many comments is a prevailing feeling in the research community that we need significantly and urgently to advance resilience research, both by sharpening concepts and theories and by conducting empirical studies at a much larger scale and with a much more extended and sophisticated methodological arsenal than is the case currently. This advancement can be achieved only in a concerted international collaborative effort. In our response, we try to argue that an explicitly atheoretical, purely observational definition of resilience and a transdiagnostic, quantitative study framework can provide a suitable basis for empirically testing different competing resilience theories (sects. R1, R2, R6, R7). We are confident that it should be possible to unite resilience researchers from different schools, including from sociology and social psychology, behind such a pragmatic and theoretically neutral research strategy. In sections R3 to R5, we further specify and explain the positive appraisal style theory of resilience (PASTOR). We defend PASTOR as a comparatively parsimonious and translational theory that makes sufficiently concrete predictions to be evaluated empirically.